A Genetic Association Test Accounting for Skewed X-Inactivation With Application to Biotherapy Immunogenicity in Patients With Autoimmune Diseases - Hässler, Signe; Camilleri-Broët, Sophie; Allez, Matthieu; Deisenhammer, Florian; Fogdell-Hahn, Anna; Mariette, Xavier; Pallardy, Marc; Broët, Philippe (Frontiers in Medicine, 2022)
Despite being assayed on commercialized DNA chips, the X chromosome is commonly excluded from GWAS analyses. One of the reasons is the complexity to analyze the data taking into account for the X-chromosome inactivation (XCI) process in women and in particular the XCI process with potential skewed pattern. This is the case when investigating the role for X-linked genetic variants in the occurrence of ADAs for patients with autoimmune diseases treated by biotherapies. In this context, we propose a novel test statistic for selecting loci of interest harbored by the X chromosome associated with time-to-event data. The proposed statistic relies on a semi-parametric additive hazard model with a latent factor and is quite easy to implement. Results from the simulation study show that the proposed test gives higher power gains as compared to the score test from the Cox model. We applied the proposed test to the data from the real-world observational multicohort study set-up by the IMI-funded ABIRISK consortium for identifying X chromosome susceptibility loci for drug immunogenicity among patients with autoimmune diseases treated by biotherapies. The proposed test allowed us to select two SNPs with high linkage disequilibrium (rs5991366 and rs5991394) located in the cytoband Xp22.2 that would have been overlooked by classical score test under the Cox model with XCI and XCE (inactivation escape) coding. Both SNPs showed a similar protective effect for the drug immunogenicity without any occurrence of ADA positivity for the homozygous females and hemizygous male for the alternative allele. To our best knowledge, this is the first study to investigate association between X chromosome loci and anti-drug antibodies occurence. We think that more X-Chromosome GWAS should be performed and that the proposed test is well-suited for identifying X Chromosome SNPs, while taking into account for all patterns of the skewed X-Chromosome inactivation process.